Theology of Mission in Pluralism dalam Kitab Yudas - Chris Sorongan; Yosep Heristyo Endro Baruno; Agustinus Pandu Wicaksono (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Theology of Mission in Pluralism, as presented in the Book of Jude, provides an understanding of God's mission (Missio Dei) that is universal and involves the Church's participation in proclaiming the Gospel amidst cultural and religious diversity. This study aims to explore the concept of theological mission found in the Epistle of Jude, particularly in the context of pluralism in culture and religion during the early Church period. Using an exegetical method and literature analysis, this research identifies that Christian mission according to Jude is not only limited to the proclamation of the Gospel but also includes the struggle against false teachings and the strengthening of the faith of the believers. The mission in the Book of Jude emphasizes the importance of showing compassion to those who are uncertain in their faith, as well as the need for decisive action to save people from the fire of judgment. Furthermore, this study reveals that the Church plays a central role as the sphere of mission, where the congregation is called to remain firm in faith and contribute to saving others from misleading teachings. Overall, the theology of mission in pluralism according to Jude teaches the importance of balancing firmness in upholding the truth with gentleness in guiding those who are uncertain.